Student Admission Strategy in Terms of The Influence of Physical Infrastructure And Sharia Marketing On The Decision To Choose A College By New Students - Refi Nabillah Royadi; Laily Dwi Arsyanti; Rizal Syarief (Enrichment : Journal of Management, 2022)
Universities have a duty to provide quality education by constantly improving the quality they have. This study aims to analyze the factors of physical infrastructure and sharia marketing to the number of new student admissions and strategies to increase the number of students enrolling in the Global Institute of Technology and Business (Global Institute). The method used in this study is a quantitative method. The data processing and analysis techniques used in this study used Structural Equation Modeling (SEM), descriptive analysis, and SWOT analysis. From the results of this study, it can be concluded that physical infrastructure has a positive effect on decisions but not significantly on the decision to choose college, while Sharia marketing has a positive and significant effect on the admission of new students. Strategies toincrease the number of students enrolling in the Global Institute include having an extensive network of cooperation with the business world and industry for internships or working both at home and abroad, the implementation of affordable tuition fees with a payment scheme can be paid in installments, the possession of a curriculum that is able to adjusting to the development of the business world and industry, improving the quality of human resources both in terms of formal and non-formal education, and making continuous improvements and maintenance of facilities and infrastructure.